Numerical-vector succession for the graphic structural analysis of masonry historic buildings with arches and symmetrical systems - Torres Montes de Oca, Carlos Alberto; Rosas Valencia, José Eduardo; Pérez Jarquín, Oswaldo Aldair (Revista ALCONPAT, 2024)
Many historic buildings have symmetry in their geometric configuration. The objective of this research is to denote the application of numerical-vector succession in the structural analysis of historical masonry buildings, with arches and symmetrical systems, including mathematical processes in ancient graphic analysis, emphasizing the importance of loads in the structural stability. We based the analysis on three fundamental stages: recognition of the construction system of the heritage object, geometric discretization of the system and vector analysis under different physical considerations. Hence, the thrust lines are affected by the loads, boundary conditions and history of structural behaviour. Numerical and computational tools offer faster and more accurate graphic analysis processes.Many historic buildings have symmetry in their geometric configuration. The objective of this research is to denote the application of numerical-vector succession in the structural analysis of historical masonry buildings, with arches and symmetrical systems, including mathematical processes in ancient graphic analysis, emphasizing the importance of loads in the structural stability. We based the analysis on three fundamental stages: recognition of the construction system of the heritage object, geometric discretization of the system and vector analysis under different physical considerations. Hence, the thrust lines are affected by the loads, boundary conditions and history of structural behaviour. Numerical and computational tools offer faster and more accurate graphic analysis processes.